Solving Examination Timetabling Problem using Partial Exam Assignment with Hill Climbing Search - Ashis Kumar, Mandal; M. N. M., Kahar (2015)
This paper describes a method that combines graph heuristics and hill climbing for addressing the examination timetable problem. In this approach, all exams are ordered with graph heuristic ordering approach and partial exams are considered for scheduling. These partial scheduled exams are then improved using hill climbing until all exams have been successfully scheduled. Various exam assignment values with different graph heuristics ordering have been investigated. The proposed approach has been tested over the twelve Toronto benchmark datasets. The experimental results and comparison with other methods demonstrate that the proposed approach is able to produce good quality timetable